The SAGE handbook of the philosophy of social sciences - Jarvie, I. C. 1937-; Zamora Bonilla, Jesus P., (SAGE Publications, 2011)
This handbook provides a comprehensive view of the fundamental philosophical and methodological problems characteristic of the social sciences, as well as of the main approaches and school of thought within the discipline. It is a reference for researchers and teachers to employ in their investigations and lectures.